Effect of age and sexual condition on the fatty acid profile of intramuscular fat of cattle finished in feedlot - CARRILHO, Charles de Oliveira; KUSS, Fernando; MOLETTA, José Luiz; MENEZES, Luís Fernando Glasenapp de (Food Science and Technology, 2023)
The objective of this study was to evaluate the fatty acid (FA) profile of intramuscular fat of cattle of two categories (16 or 26 months old) and two sexual conditions (Bulls or Steers) finished in feedlot. A total of 32 castrated (n=16) or noncastrated (n=16) animals of the genetic groups ½Purunã + ½Canchim were used. The animals were finished in feedlot, receiving a diet with 50% roughage and 50% concentrated feed. After the slaughter, one Longissimus dorsi sample from each animal was sent to the laboratory for FA profile analyses. The FA content of C17:0 iso and C18:0 was higher for animals slaughtered at 26 months. Lignoceric acid (C24:0) showed a higher content for animals aged 16 months. Animals slaughtered at 16 months showed higher C18:1 cis 11, C18:1 cis 12, C18:1 cis 15, and lower C18:1 trans 16 than those slaughtered at 26 months. The C20:4 and C22:5 were lower as the animals’ slaughter age increased. The unsaturated/saturated and polyunsaturated/saturated ratios showed no difference for slaughter age. The concentrations of C24:0, C18:1 trans 10, C18:1 cis 11, C18:1 cis 12, and C22:1 were greater in the meat of bulls than in steers. Bulls had a higher content of polyunsaturated FAs and polyunsaturated/saturated ratio than steers.